2017
DOI: 10.3390/sports5030055
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Effects of Isometric Handgrip Exercise on Cardiovascular Variables in Hypertensive Patients: A Systematic Review

Abstract: The aim of this study was to describe, through a systematic review, the acute and chronic effects of isometric handgrip exercise on cardiovascular variables in hypertensive individuals. In this systematic review, we included studies that analyzed whether a single bout or a program with isometric exercises affect cardiovascular variables in hypertensive adults. The electronic database PubMed/Medline was searched for relevant studies published until May 2017. Of the 2927 studies initially identified, 2916 were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 26 publications
(55 reference statements)
3
36
1
7
Order By: Relevance
“…O treinamento isométrico com handgrip tem sido proposto como alternativa para o tratamento e a prevenção da hipertensão arterial sistêmica, uma vez que estudos de revisão e meta-análises têm demonstrado que esse tipo de treinamento promove reduções da pressão arterial (PA) [1][2][3] . American Heart Association 4 já começa a indicar, embora com cautela, os potenciais benefícios desse tipo de treinamento.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…O treinamento isométrico com handgrip tem sido proposto como alternativa para o tratamento e a prevenção da hipertensão arterial sistêmica, uma vez que estudos de revisão e meta-análises têm demonstrado que esse tipo de treinamento promove reduções da pressão arterial (PA) [1][2][3] . American Heart Association 4 já começa a indicar, embora com cautela, os potenciais benefícios desse tipo de treinamento.…”
Section: Introductionunclassified
“…Curiosamente, os estudos que analisaram as respostas agudas utilizaram o protocolo de 30% da CVM, sendo desconhecidos efeitos cardiovasculares com outras intensidades, embora cronicamente a intensidade de 50% da CVM se mostre eficaz na redução da PA 13 . Além disso, cronicamente o aumento da modulação do parassimpático concomitantemente com a redução do simpática para o coração vem sendo sugerido como mecanismo responsável da redução da PA após treinamento com handgrip 3,14 , o que corrobora com as respostas agudas encontradas em idosos 15,16 e jovens 17 . Por outro lado, se diferentes intensidades também modulariam as respostas da modulação autonômica cardíaca é desconhecido.…”
Section: Introductionunclassified
“…Badrov et al (2013) did not report any adverse events after 8 weeks of training. Studies have observed a modest increase in heart rate (Δ = 3 ± 4 bpm), systolic blood pressure (Δ = 16 ± 10 mm Hg) and diastolic blood pressure (Δ + 7 ± 6 mm Hg) during isometric exercise (Araujo et al, 2011), as well as no significant changes after the exercise (Farah et al, 2017;Silva et al, 2018;Silva et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the well‐established long‐term effects of isometric handgrip training on blood pressure (Badrov et al, ; Cahu Rodrigues et al, ; Carlson et al, ; Farah et al, ; Farah et al, ; Millar et al, ; Silva et al, ; Taylor et al, ), the effects of this training mode on cardiac autonomic modulation are controversial (Badrov et al, ; Farah et al, ; Millar et al, ; Stiller‐Moldovan et al, ; Taylor et al, ). Taylor et al () noted marked improvements in high‐frequency spectral power in uncontrolled hypertensives after 10 weeks isometric handgrip training.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, it is seen as an indispensable element and a cornerstone in the nonpharmacological therapy of the cardiovascular, metabolic, and osteomuscular disorders [1]. Nowadays, scientists are engaged in finding the optimal intensity of physical activity in order to promote health and lifespan, improve quality of life, and decrease the incidence of lifestyle-related diseases [2,3]. Moderateintensity training (MIT) represents a training method involving longer-duration sessions of moderate-intensity exercise performed continuously without rest [4].…”
Section: Introductionmentioning
confidence: 99%